Implementasi Metode Certainty Factor Dalam Sistem Pakar Diagnosis Awal Tanda Bahaya Gangguan Menstruasi - Andreswari, Desi; Erlansari, Aan; Coastera, Funny Farady; Hasian Lumbanraja, Joi Pebrianty (Rekursif: Jurnal Informatika, 2023)
Menstrual disorders are disorders that occur in the menstrual cycle including changes that occur in the cycle, blood count, and other changes related to the menstrual cycle. Most women do not feel symptoms at the time of menstruation, but a small percentage feel pain. Menstrual disorders or also called abnormal uterine bleeding is a complaint that often causes a woman to come to the doctor for immediate treatment. Complaints of menstrual disorders vary from mild to severe. To help overcome these obstacles, expert systems can be a solution. This expert system was created using the certainty factor method consisting of 46 symptoms with 12 types of diseases. This system produces output in the form of a percentage of the type of possible diagnosis of the disease experienced by the user and suggestions based on the symptoms experienced by the user. The functionality testing process of this expert system went well using black box testing and resulted in 100% functional success. Evaluation of the accuracy of the certainty factor method for diagnosing menstrual disorders resulted in an accuracy rate of 84.61%. Keywords: Menstruation, Menstrual disorders, Certainty Factor, Expert System, Diagnosis